Deconvolution of the hematopoietic stem cell microenvironment reveals a high degree of specialization and conservation - Jin Ye; Isabel A. Calvo; Itziar Cenzano; Amaia Vilas; Xabier Martinez-de-Morentin; Miren Lasaga; Diego Alignani; Bruno Paiva; Ana C. Viñado; Patxi San Martin-Uriz; Juan P. Romero; Delia Quilez Agreda; et al. (iScience, 2022)
Summary: Understanding the regulation of normal and malignant human hematopoiesis requires comprehensive cell atlas of the hematopoietic stem cell (HSC) regulatory microenvironment. Here, we develop a tailored bioinformatic pipeline to integrate public and proprietary single-cell RNA sequencing (scRNA-seq) datasets. As a result, we robustly identify for the first time 14 intermediate cell states and 11 stages of differentiation in the endothelial and mesenchymal BM compartments, respectively. Our data provide the most comprehensive description to date of the murine HSC-regulatory microenvironment and suggest a higher level of specialization of the cellular circuits than previously anticipated. Furthermore, this deep characterization allows inferring conserved features in human, suggesting that the layers of microenvironmental regulation of hematopoiesis may also be shared between species. Our resource and methodology is a stepping-stone toward a comprehensive cell atlas of the BM microenvironment.